On the boundary conditions for products of Sturm-Liouville differential operators - Ibrahim, Sobhy El-Sayed (Tamkang Journal of Mathematics, 2001)
In this paper, the second-order symmetric Sturm-Liouville differential expressions τ_1, τ_2, …, τ_n with real coefficients are considered on the interval I = (a,b) , - ∞ a < b ∞ . It is shown that the characterization of singular self-adjoint boundary conditions involves the sesquilinear form associated with the product of Sturm-Liouville differential expressions and elements of the maximan domain of the product operators, and is an exact parallel of the regular case. This characterization is an extension of those obtained in [6], [8], [11-12], [14] and [15].